Polyamines interfere with protein ubiquitylation and cause depletion of intracellular amino acids: a possible mechanism for cell growth inhibition. Issue 2 (7th December 2018) - Sayas, Enric; Pérez‐Benavente, Beatriz; Manzano, Concepción; Farràs, Rosa; Alejandro, Santiago; del Pozo, Juan Carlos; Ferrando, Alejandro; Serrano, Ramón
Abstract : Spermidine is a polyamine present in eukaryotes with essential functions in protein synthesis. At high concentrations spermidine and norspermidine inhibit growth by unknown mechanisms. Transcriptomic analysis of the effect of norspermidine on the plant Arabidopsis thaliana indicates upregulation of the response to heat stress and denatured proteins. Accordingly, these polyamines inhibit protein ubiquitylation, both in vivo (in yeast, Arabidopsis, and human Hela cells) and in vitro (with recombinant ubiquitin ligase). This interferes with protein degradation by the proteasome, a situation known to deplete cells of amino acids. Norspermidine treatment of yeast cells induces amino acid depletion, and supplementation of media with amino acids counteracts growth inhibition and cellular amino acid depletion but not inhibition of protein polyubiquitylation. Abstract :